Ensaios de tratabilidade aplicados a determinação de parâmetros para dimensionamento de processos de tratamento de água de manancial eutrofizado - Eustáquio, Hugo Mozer Barros (2010)
Eutrophication is a growing process present in the water sources located in the northeast of Brazil. Among the main consequences of these changes in trophic levels of a water source, stands out adding complexity to the treatment to achieve water standards. By these considerations, this study aimed to define, on a laboratory scale, products and operational conditions to be applied in the processing steps using raw water from Gargalheiras dam, RN, Brazil. The dam mentioned shows a high number of cyanobacteria, with a concentration of cells / ml higher than that established by Decree No. 518/04 MS. The same source was also considered by the state environmental agency in 2009 as hypereutrophic. The static tests developed in this research simulated direct filtration (laboratory filters) and pre-oxidation with chlorine and powdered activated carbon adsorption. The research included the evaluation of the coagulants aluminum hydrochloride (HCA) and alum (SA). The development of the research investigated the conditions for rapid mixing, the dosages of coagulants and pHs of coagulation by the drawing of diagrams. The interference of filtration rate and particle size of filtering means were evaluated as samples and the time of contact were tested with chlorine and activated carbon. By the results of the characterization of the raw water source it was possible to identify the presence of a high pH (7.34). The true color was significant (29 uH) in relation to the apparent color and turbidity (66 uH and 13.60 NTU), reflecting in the measurement of organic matter: MON (8.41 mg.L-1) and Abs254 (0.065 cm-1). The optimization of quick mix set time of 17", the speed gradient of 700 s-1 in the coagulation with HCA and the time of 20" with speed gradient of 800 s-1 for SA. The smaller particle sizes of sand filtering means helped the treatment and the variation in filtration rate did not affect significantly the efficiency of the process. The evaluation of the processing steps found adjustment in standard color and turbidity of the Decree nº 518/04 MS, taking in consideration the average values found in raw water. In the treatment using the HCA for direct filtration the palatable pattern based on the apparent color can be achieved with a dose of 25 mg L-1. With the addition of pre-oxidation step, the standard result was achieved with a reduced dose for 12 mgHCA.L-1. The turbidity standard for water was obtained by direct filtration when the dose exceeds 25 mg L-1 of HCA. With pre-oxidation step there is the possibility of reducing the dose to 20 mg L-1.The addition of CAP adsorption, promoted drinking water for both parameters, with even lower dosage, 13 mg L-1 of HCA. With coagulation using SA removal required for the parameter of apparent color it was achieved with pre-oxidation and 22 mgSA.L-1. Despite the satisfactory results of treatment with the alum, it was not possible to provide water with turbidity less than 1.00 NTU even with the use of all stages of treatment